Impact of tobacco smoke constituents on nicotine-seeking behavior in adolescent and adult male rats - Gellner, Candice A.; Carreño, Diana; Belluzzi, James D.; Leslie, Frances M. (Frontiers in Psychiatry, 2023)
Given the rapid increase in teen vaping over recent years it is critical to understand mechanisms underlying addiction and relapse to tobacco use at this age. To evaluate the role of non-nicotine constituents in cigarette smoke, our lab has previously established a model of intravenous self-administration of aqueous cigarette smoke extract (CSE). We now compare the sensitivity of male adolescent and adult rats who have self-administered CSE or nicotine to reinstatement with the pharmacological stressor, yohimbine, with and without cues. Adolescents and adults, aged postnatal day (P) 34 and 84, were tested for the effect of yohimbine (0 – 2.5 mg/kg) on plasma corticosterone levels to establish a dose that was an effective stressor at both ages. Separate groups of animals were trained to lever press for food before beginning 1-hour drug self-administration sessions for nicotine or CSE (15 µg/kg/infusion nicotine content). Once stable responding was reached, drug was removed, and behavior extinguished. Drug-seeking behavior was reinstated with yohimbine, cues, or a combination of yohimbine and cues. Although adolescents and adults showed different dose-responses for yohimbine-induced corticosterone release, a dose of 2.5 mg/kg increased stress hormone levels at both ages. Whereas both ages displayed similar responding for CSE and nicotine, adolescents self-administered more CSE and nicotine as compared to adults. Cues and cues + stress reinstated responding to a greater extent in animals that had self-administered CSE, regardless of age. These findings suggest that non-nicotine tobacco smoke constituents influence later but not earlier stages of addiction in both adolescent and adult male rats.